Piezoelectric beta-PVDF polymer films as fluid acoustic microagitator - Cardoso, V. F. (2008)
The main objective of this paper is to describe a fluidic acoustic microagitation system based on a Poly(Vinylidene Fluoride) polymer. This system benefits from the high piezoelectric properties presented by the beta-phase of the polymer (beta-PVDF) converting an electrical signal into acoustics vibrations. These vibrations can be used in microfluid systems to enhance fluids mixture and reaction. Experimental results regarding the influence of the area and thickness of the piezoelectric beta-PVDF polymer on the velocity of reaction of some biological fluids are presented. Moreover, the incorporation of the beta-PVDF underneath microfluidic structures of a lab-on-a-chip with an automatic electronic control is referred.